Family needs and psychosocial functioning of caregivers of individuals with spinal cord injury from Colombia, South America (2010)
Objective: 1) To determine the most frequent needs in a group of family caregivers of individuals with spinal cord injury in Neiva Colombia; 2) to describe caregivers' psychosocial functioning; and 3) to examine the relationship between caregiver needs and caregiver psychosocial functioning. Design: Cross-sectional. Participants/Methods: 37 caregivers completed a caregiver needs questionnaire composed of 27 questions (1-5 scale) and 9 sub-scales (emotional, information, economic, community, and household support, respite, physical health, sleep, and psychological health). The Patient Health Questionnaire (PHQ-9) was used to measure caregiver depression, the Zarit Burden Interview (ZBI) measured stress, the Interpersonal Support Evaluation List Short Version (ISEL-12) measured social support, and the Satisfaction With Life Scale (SWLS) was used to assess satisfaction with life. Results: Information, economic, emotional, community support, and respite needs were most frequently reported among this group of Colombian caregivers. Forty-three percent of the family caregivers reported some level of depression, 68% reported being overwhelmed by their caretaking responsibilities, and 43% reported dissatisfaction with their lives. Information, emotional, economic, physical, sleep, and psychological needs were positively correlated with depression and burden. Those with more household, physical, sleep, economic, and psychological needs had less satisfaction with life and social support. Caregivers with more community and respite needs had less social support, while those with more emotional needs had less satisfaction with life. Caregivers with more respite needs had more burden and those with more household needs had more depression. Conclusion: Approximately half of the sample reports some level of burden, depression, or being dissatisfied with life. Psychosocial functioning was related to various family needs. Further longitudinal research is needed to determine whether caregivers with more needs report worse psychosocial functioning or if those with worse psychosocial functioning report more needs. © 2010 - IOS Press and the authors. All rights reserved.